Higher Intake of Sulfur Amino Acids Is Associated with Greater Mortality Among US Adults: NHANESIII Cohort Study (P18-061-19). (13th June 2019) - Dong, Zhen; Gao, Xiang; Chinchilli, Vernon; Muscat, Joshua; Richie, John
Abstract: Objectives: Preclinical evidence has suggested that low consumptions of sulfur amino acids (SAA) methionine (Met) and cysteine (Cys) are associated with a variety of health benefits including delayed aging and lower incidence of aging-related diseases including diabetes. Further, in the United States, the average person consumes SAA at levels far in excess of the Recommended Dietary Allowance (RDA) and a variety of negative effects of excess SAA intake have been reported. However, there is little data regarding the relationship between SAA intake and health status in humans. We thus prospectively analyzed the associations between SAA intake and all-cause and disease-specific mortality rates in a large cohort of US adults participating in the Third National Examination and Nutritional Health Survey (NHANES III) Study. Methods: Dietary intake of SAA was assessed via a 24-h recall questionnaire. Mortality cases were assessed via search in the National Death Index. Hazard ratios (HR) were calculated from Cox proportional hazards models to evaluate associations between intakes of SAAs intake (in quintiles) and risk of mortality. Models were adjusted for age, sex, body mass index (BMI), smoking, alcohol intake, dietary factors, and disease history. Results: A total of 3594 mortality events out of 12, 395 eligible participants occurred during 23 years of follow-up. After full adjustment, absolute intake of higher Met, Cys, and total SAA were associated with increases in all-cause mortality (HR = 1.13 (1.00–1.13), 1.15 (1.01–1.30), 1.13 (1.00–1.27), respectively), and in diabetes mortality (HR = 3.00 (1.53–5.70), 3.26(1.65–6.46), 3.81(1.87–7.77), respectively). No associations were found with other causes of mortality. When SAA intake was expressed as protein density, only Cys and total SAA intake were positively associated with increased diabetes mortality ( P < 0.02). Conclusions: Overall, these data support our hypothesis that higher consumption of SAA is associated with increased mortality. Given the high intake of SAA among the US population, our findings may have important public health implications. Funding Sources: This study was not externally funded. Supporting Tables, Images and/or Graphs: